Cutaneous information processing differs with load type during isometric finger abduction - Yunoki, Keisuke; Watanabe, Tatsunori; Matsumoto, Takuya; Kuwabara, Takayuki; Horinouchi, Takayuki; Ito, Kanami; Ishida, Haruki; Kirimoto, Hikari (PLOS ONE, 2022)
During submaximal isometric contraction, there are two different load types: maintenance of a constant limb angle while supporting an inertial load (position task) and maintenance of a constant force by pushing against a rigid restraint (force task). Previous studies demonstrated that performing the position task requires more proprioceptive information. The purpose of this study was to investigate whether there would be a difference in cutaneous information processing between the position and force tasks by assessing the gating effect, which is reduction of amplitude of somatosensory evoked potentials (SEPs), and cutaneomuscular reflex (CMR). Eighteen healthy adults participated in this study. They contracted their right first dorsal interosseous muscle by abducting their index finger to produce a constant force against a rigid restraint that was 20% maximum voluntary contraction (force task), or to maintain a target position corresponding to 10° abduction of the metacarpophalangeal joint while supporting a load equivalent to 20% maximum voluntary contraction (position task). During each task, electrical stimulation was applied to the digital nerves of the right index finger, and SEPs and CMR were recorded from C3’ of the International 10–20 system and the right first dorsal interosseous muscle, respectively. Reduction of the amplitude of N33 component of SEPs was significantly larger during the force than position task. In addition, the E2 amplitude of CMR was significantly greater for the force than position task. These findings suggest that cutaneous information processing differs with load type during static muscle contraction.